Rare heterozygous parkin variants in French early-onset Parkinson disease patients and controls. Issue 1 (31st August 2007) - Lesage, S; Lohmann, E; Tison, F; Durif, F; Dürr, A; Brice, A; ,
Abstract : Background: Mutations in the parkin gene cause autosomal recessive early-onset parkinsonism. The effect of single heterozygous mutations in parkin is still unclear. The aim of this study was to evaluate the frequency of exonic parkin variants in a case–control study. Methods: The parkin gene was screened for both point mutations and exon rearrangements in 172 French patients with Parkinson disease (PD) and 170 controls from the same population. Patients with single parkin variants were also screened for PINK1, DJ-1 and LRRK2 exon 41 mutations. Results: 10 exonic sequence variations were identified, including 3 known polymorphisms and 7 rare heterozygous variants, 2 of which were novel. There were significantly more rare heterozygous variants in patients (n = 10) with early-onset PD than in controls (n = 2). Screening of PINK1, DJ-1 and LRRK2 exon 41 in the 10 patients heterozygous for parkin failed to identify a second causative mutation. Conclusion: These results suggest that single parkin mutations increase the risk of early-onset PD, but the possibility of a second parkin mutation cannot be excluded.